(untitled) (Eurasian Journal of Ecology, 2018)
Study algocenoses of the lake Bilikol showed a preponderance of green algae on toxin and blue-green microalgae by frequency of occurrence. Species diversity of certain microalgae lake Bilikol belonged to the 4 divisions, 9 classes, 9 orders, 17 families, 36 genera and 102 species. High species richness differed in the phytoplankton of the lake Bilikol green and blue-green algae, their number of species, varieties and forms is slightly more than half of the taxonomic list (60% of the total). Cyanobacteria in the phytoplankton of the lake Bilikol ranked second in species richness, and of the first. As a result of the analysis of certain types of indicator-saprobity cyanobacteria lake Bilikol we identified 12 species and varieties of indicator species of cyanobacteria. Modern combination chromatography and mass spectrometry are the most sensitive and selective methods of analysis of natural toxins, providing reliable identification. HPLC extracts of dried biomass of plank tonic algae identified in lake Bilikol three structural variants hepatotoxic microcystins: Microcystin-RR, 7-Demethylmicrocystin RR and Microcystin-LR. Judging from the largest peak at chromatograms, in the study of biomass is dominated by Microcistina-LR. The presence of phytoplankton biomass microcystins in summer, obviously, connected with the active development of cyanobacteria from birth by Microcystis, Anabaena, etc. It was determined that the «flowering» of the water of the lake Bilikol is not valid as recreational reservoirs, because it threatens the health of people and animals. Key word: toxin, cyanobacteria, microalgae, algoflora, algocenos.